CONCRETE DAMAGE ASSESSMENT THROUGH IMAGE PROCESSING WITH CANNY EDGE DETECTION METHOD - Endru Suphato Sendiko; Henny Wiyanto (JMTS: Jurnal Mitra Teknik Sipil, 2022)
Concrete damage assessment for further action is very important for the safety of building strength before something unexpected happens. Therefore, an early assessment of a building that might seem alarming is very important. There are many methods that can be used to assess concrete damage, starting from the visual, use of tools, destructive and non-destructive test. As the rapid development of infrastructure, there is also an increase need to assess the damaged concrete. Not only new buildings, old buildings also need to be assessed to ensure the safety of these buildings, especially buildings affected by earthquakes, natural disasters, dirty environments and or others. The high need for assessors in these locations become a problem if the building is huge and will take time if done with a small workforce, technological assistance is the solution. Buildings affected by natural disasters causes various kinds of damage, starting from cracks, mold and stains on concrete blankets. This damage can interfere with the strength and safety of the building, so assessing damage to concrete is very important. Not all buildings that are damaged are safe to go to, let alone stepped on, so we need the help of technology, for example cameras or drones.